Numerical assessment for the efficiencies of check dams in debris flow gullies: A case study. (June 2020) - Shen, Wei; Li, Tonglu; Li, Ping; Lei, Yulu
Abstract: Quantitative assessment for the efficiencies of check dams is necessary for the purpose of reducing the risk of potential debris flow disasters. In this paper, an improved finite difference model is adopted to assess the efficiency of the check dam in Dagou debris flow gully, Gansu Province, China. Unlike other numerical models, the improved model can simultaneously consider bed entrainment and the impeding effect of check dams, so it can reflect the interaction between check dams and debris flow dynamics. The results show that the existing 10 m check dam may only be sufficient to prevent a debris flow with less than 0.8 times the volume of the catastrophic event occurred in this gully in 2013. Otherwise, a higher check dam should be constructed in order to prevent a larger event. The location of a check dam has significant influence on the dynamics of the debris flow. Generally, a check dam constructed in the upper part of the gully performs better in controlling bed entrainment and the discharge. Comparing with the locations in downstream, the dam site located in upstream of this gully seems to be a better choice in terms of both efficiency and engineering quantity.